Philippine rice and rural poverty: an impact analysis of market reform using CGE - Cororaton, Caesar B. (International Food Policy Research Institute, 2006)
This paper looks at how Philippine trade reform which consists of tariff reduction and elimination of quantitative restrictions (QR) on rice imports will affect poverty within two world trade scenarios: Doha and free world trade. The impact of Doha is very small and generates biased effects against agriculture. The impact of Philippine trade reform within the Doha agenda magnifies this biased effect, making rural households worse-off compared to urban households. However, eliminating rice QR generates a set of effects where consumer price reduction dominates nominal income decline. Thus, real income improves and poverty declines across household groups, but the net effects are lower in rural than in urban households. The impact of a free world trade economy is favorable in terms of higher export prices and export demand for agriculture and agriculture-related manufacturing industries. This mitigates the biased effects against agriculture, and is therefore favorable to rural households. However, if Philippine trade reform is added to the analysis, the result switches back to the previous biased effects on agriculture and on rural households.